Azjatycki model integracji gospodarczej na przykładzie działalności ASEAN w kontekście RCEP – studium polityczno-prawne - Orfin, Tomasz (Katedra Doktryn Politycznych i Prawnych Wydziału Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2021)
The subject of the paper is to present the issues of Southeast Asia in the context of Associa-tion of Southeast Asian Nations (ASEAN). The main emphasis was placed on the presentation selected political, economic and legal issues related to the economic and political integration of ASEAN member states. The text also discusses the influence of China and Japan on the policies of the Association and individual member states as well as the concept of economic cooperation promoted by these countries. Legal and political analysis is subject to the Regional Comprehensive Economic Partnership (RCEP) as the culmination of a stage of integration and cooperation in the region, which fully reflects the specificity of Southeast Asia. This analysis is based on the current political and legal context.
Keywords: ASEAN; RCEP; Azja; integracja